2018
DOI: 10.5152/iao.2018.3977
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Stimulus Intensity in Transcutaneous Vagus Nerve Stimulation for Chronic Tinnitus

Abstract: OBJECTIVES:We aimed to assess the clinical significance of the intensity of transcutaneous vagus nerve stimulation (tVNS) in chronic tinnitus. MATERIALS and METHODS:Four sessions of tVNS were performed over a 2-week period for 24 patients with unilateral, non-pulsatile chronic tinnitus. The cavum, cymba, and tragus were sequentially stimulated to the maximal sensory thresholds. One month later, after the four sessions, the level of tinnitus distress and changes in stimulus intensity were assessed. RESULTS:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…To date, there have only been a limited number of small and uncontrolled pilot studies to assess the safety and efficacy of bimodal neuromodulation approaches employing sound stimulation combined with cranial nerve stimulation for tinnitus treatment. These include invasive vagus nerve stimulation [41,53], noninvasive stimulation of the vagus nerve [54-56], and noninvasive cervical or trigeminal nerve stimulation [42-44,46,47]. Although the vagus nerve stimulation demonstrated promising results in animals [37], human studies have shown mixed results [41,53].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have only been a limited number of small and uncontrolled pilot studies to assess the safety and efficacy of bimodal neuromodulation approaches employing sound stimulation combined with cranial nerve stimulation for tinnitus treatment. These include invasive vagus nerve stimulation [41,53], noninvasive stimulation of the vagus nerve [54-56], and noninvasive cervical or trigeminal nerve stimulation [42-44,46,47]. Although the vagus nerve stimulation demonstrated promising results in animals [37], human studies have shown mixed results [41,53].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 9 included primary studies, 5 used transcutaneous VNS treatment [ 16 20 ] compared to 4 studies with implanted VNS [ 21 24 ]. In 6 out of 9 studies the VNS treatment was combined with sound therapy(ST) [ 17 , 18 , 20 , 22 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Suk et al performed a prospective cohort study in 2018 in which 24 patients with a tinnitus duration of ≥3 months received four sessions of transcutaneous VNS over a two week period [ 16 ]. In these sessions, the cavum, cymba, and tragus were subsequently stimulated to the maximal sensory thresholds, this being the threshold that could be tolerated without any painful sensation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows identical stimulus waveforms (low panels) between the onset and the offset of the 10-min electric stimulation, suggesting that perceptual changes in both loudness adaptation and tinnitus suppression (upper panel, the same data as T10 in Figure 6) are unrelated to any changes in physical stimulation but rather related to central changes in the nervous system. One possible mechanism is direct stimulus-induced neuroplasticity (e.g., Jackson, Mavoori, & Fetz, 2006; Weisz et al., 2007; Zeng et al., 2011) while another possible mechanism is indirect neuromodulation via vagus nerve stimulation (e.g., Engineer et al., 2011; Kreuzer et al., 2014; Suk, Kim, Chang, & Lee, 2018). At present we do not know the exact mechanisms, nor do we know whether the presently observed short-term tinnitus suppression can translate into a long-term tinnitus therapy.…”
Section: Discussionmentioning
confidence: 99%